Application of Synthetic Polymeric Scaffolds in Breast Cancer 3D Tissue Cultures and Animal Tumor Models. (17th December 2017) - Rijal, Girdhari; Bathula, Chandra; Li, Weimin
Abstract : Preparation of three-dimensional (3D) porous scaffolds from synthetic polymers is a challenge to most laboratories conducting biomedical research. Here, we present a handy and cost-effective method to fabricate polymeric hydrogel and porous scaffolds using poly(lactic-co-glycolic) acid (PLGA) or polycaprolactone (PCL). Breast cancer cells grown on 3D polymeric scaffolds exhibited distinct survival, morphology, and proliferation compared to those on 2D polymeric surfaces. Mammary epithelial cells cultured on PLGA- or PCL-coated slides expressed extracellular matrix (ECM) proteins and their receptors. Estrogen receptor- (ER-) positive T47D breast cancer cells are less sensitive to 4-hydroxytamoxifen (4-HT) treatment when cultured on the 3D porous scaffolds than in 2D cultures. Finally, cancer cell-laden polymeric scaffolds support consistent tumor formation in animals and biomarker expression as seen in human native tumors. Our data suggest that the porous synthetic polymer scaffolds satisfy the basic requirements for 3D tissue cultures both in vitro and in vivo . The scaffolding technology has appealing potentials to be applied in anticancer drug screening for a better control of the progression of human cancers.